The Versatility of the Superficial Circumflex Iliac Artery Perforator Flap: A Single Surgeon's 16-Year Experience for Limb Reconstruction and a Systematic Review - Berner, Juan Enrique; Nikkhah, Dariush; Zhao, Jade; Prousskaia, Elena; Teo, Tiew Chong (Journal of Reconstructive Microsurgery, 2020)
Background The superficial circumflex iliac artery perforator (SCIP) flap is a versatile option of free tissue transfer for small to large defects. In this study, we examine the advantages of the SCIP flap, its cadaveric anatomy, and clinical subtypes.Methods Ten cadavers were dissected and the corresponding pedicles of the SCIP and groin flaps were identified. A retrospective review of 20 clinical cases of free SCIP flap reconstruction was undertaken. The indication for reconstruction, flap dimensions, and survival were analyzed. A systematic literature review was conducted including articles that have previously reported the use of the SCIP flap.Results The SCIP pedicle was present in all our cadaveric dissections. The starting point of its pedicle ranged from 1.5 to 4.5 cm along the superficial circumflex iliac artery. The median diameter of the perforator and its concomitant vein was 1mm (range 0.8–2 mm). A cutaneous vein (1.3–2.3 mm) could be included in the flap if the concomitant vein was too small. Twenty consecutive patients had free SCIP flaps between 2002 and 2018. The indications were for finger defects (n = 8), thumb reconstruction (n = 1), lower limb compound fractures (n = 3), iatrogenic wounds (n = 2), upper limb large defects (n = 2), and scar contractures (n = 4). Flap dimensions ranged from 2 × 4 cm to 14 × 25cm, and the longest pedicle was 8cm. All flaps survived. The systematic literature review identified 34 previous reports using the SCIP flaps, most of these published by Asian units.Conclusion The SCIP flap is useful for reconstruction throughout the body due to its ease of dissection, thinness, adjustable pedicle length, and flap dimension ranging from tiny to large, as well as the feasibility of raising a compound flap incorporating an adipofascial or vascularized bone component if necessary.This is a level of evidence therapeutic IV study.
Keywords: anatomy; free tissue transfer; limb reconstruction